Spanish territorial autonomy in the perspective of Poland = Hiszpańska autonomia terytorialna w perspektywie Polski - Iwanek, Jan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Despite the significant experiences of territorial autonomy of the province of Silesia in the Second Republic, in the current political system of Poland the extent of decentralization of the state is lim-ited. The mainstream of political elites do not provide for changes in this area. Nevertheless, it is worth getting to know the experiences of Spain, which can be a positive or negative reference for a possible projection of a political change in Poland.
Keywords: Silesia autonomy; decentralization; territorial autonomy; regionalism; autonomous state; autonomia Śląska; decentralizacja; autonomia terytorialna; regionalizm; państwo autonomiczne